Institutional Arrangements in Mangrove Rehabilitation Management of Palaui Island Protected Landscape and Am Seascape (PIPLS), Sta. Ana, Cagayan, Philippines - Calicdan, Melanie A. (Journal of Environmental Science and Management, 2016)
Sound and effective mangrove management can be achieved when the institutional stakeholders are well organized under a balanced arrangement. This paper alined to present the case of Protected Area Management Board (PAMB) of Palaui Island Protected Landscape and Seascape (PIPLS) in terms of stakeholder's role, interaction, and efforts to address problems and issues on mangrove management. Key informant interviews (KII's) in 14 institutions using a structured questionnaire were employed. The responses were validated in the field through community interview using unstructured questions. Stakeholder analysis was used to analyze the result of the interview. The interaction is only apparent among some stakeholders as far as mangrove management is concerned. Strong interaction was observed among some stakeholders while others have weak or no interaction. Stakeholders with weak interaction are those who do not have the jurisdiction on the resource while those with no interaction are stakeholders with no defined roles on mangrove management. Strong interaction was observed among stakeholders whose mandate is in line with the protection of the resource and has clear roles. Problems on the enforcement (i.e. lack of manpower and resources, inaccessibility of the administering authority, and overlapping institutional roles) still persist but coordination, consultation, and collaboration are being exercised by PAMB members to prevent further confession and successfully manage the resource. However; the weak implementation of laws due to humanitarian reasons may hamper the effectiveness of enforcement which eventually affects the successful and sound management of mangroves. Therefore, these problems should be immediately addressed. The functions of the members were only stated during the survey and interview and these shall still be subjected to further analysis to come up with a more organized and systematic development of mangrove management in PIPLS.